PENERAPAN KONSEP DASAR PENDIDIKAN PRA SEKOLAH MENUJU PENDIDIKAN DASAR PADA PESERTA DIDIK - Kausari, Dini; Susanti, Novi; Agusti, Sarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Early childhood education (PAUD) has a very important role in preparing students to enter basic education. Preschool education aims to develop children's potential holistically, including cognitive, social, emotional, and physical aspects, so that children can grow and develop towards maturity and independence. However, the implementation of the basic concept of pre-school education in Indonesia still faces various challenges, such as limited facilities, infrastructure, and the quality of educators in certain areas. In addition, the role of parents and the community in supporting early childhood education also greatly influences children's readiness to enter basic education. This study aims to examine how the implementation of the basic concept of pre-school education affects children's readiness to face basic education. The results of the study indicate that the implementation of a comprehensive child development-based curriculum, which includes literacy, numeracy, and social skills development, has a positive effect on children's readiness. However, there is variation in the quality of the implementation of pre-school education which is influenced by available resources and parents' understanding of the importance of early education. Recommendations for this study include improving the quality of educator training, providing adequate facilities and infrastructure, and strengthening the role of parents in supporting children's education. With these steps, pre-school education is expected to be a strong foundation to face the challenges of basic education.